Polyoxometalates as redox mediators for Li-air batteries - Castle, Jack (2019)
This report will walk through the process of developing polyoxometalates (POMs) to be used as redox mediators in Li – air batteries.Three POMs; (TBA)4[PW11VO40], (TBA)4[PMo11VO¬40] and (TBA)5[PMo10V2O40] were successfully synthesised and electrochemically characterised. With the redox chemistry of the POMs determined, they were implemented into working cells. Two of the three POMs resulted in an increase in capacity but had little to no effect on the reduction of the overpotential. One POM was taken forward for testing within a pressure cell, with the resulting data providing information regarding electronic efficiency and side reactions within the cell during the discharge process. It was determined that in order for POMs to be used as redox mediators, some degree of optimisation will be necessary, more specifically, tuning the redox chemistry to potentials more closely associated with Li2O2 oxidation and enhancing the solubility of the compound.